Self-Other Differences in Perceiving Why People Eat What They Eat - Sproesser, Gudrun; Klusmann, Verena; Schupp, Harald T.; Renner, Britta (Frontiers in Psychology, 2017)
People often view themselves more favorably than others, displaying unrealistic optimism. In the present study, we investigated whether people perceive their reasons for eating as better than those of others. Furthermore, we investigated which mechanisms of inaccuracy might underlie a possible bias when perceiving why people eat what they eat. In Study 1, 117 participants rated the social desirability of eating motives. In Study 2, 772 participants provided information on their own and others’ motives for eating behavior. In Study 1, particularly desirable motives were eating because of hunger, health reasons, and liking. Particularly undesirable motives were eating to make a good impression, to comply with social norms, and to regulate negative affect. Study 2 revealed that for socially desirable motives, participants perceived their own motives to be stronger; for undesirable motives, the opposite pattern emerged, with others being attributed stronger motives. Moreover, the perception of others’ emotional and social motives varied with participants’ own healthy eating behavior. Since the perception of eating motives of others should be independent of one’s own behavior, this pattern of results indicates a relative inaccuracy in the perception of others’ eating motives. In conclusion, there is evidence for unrealistic optimism in eating motives. For social and emotional motives, this self-favoring view seems to be driven by a relatively inaccurate perception of others.